Parental Involvement In The Schooling Process For Students’ Academic Success: A Case Study In The State Of Katsina, Nigeria - Ibrahim, Ahamed Tijjani (2012)
Kajian ini didorong oleh isu penglibatan ibu bapa dalam proses persekolahan kanak-kanak di Katsina yang seolah-olah diabaikan.